Development of Nutrition Instruments for Women to Prevent Early Stunting: A Systemic Literature Review - Setyawati, Vilda Ana Veria; Yuniastuti, Ari; Handayani, Oktia Woro Kasmini; Farida, Eko (Jurnal Kesehatan Masyarakat, 2024)
This study aims to provide an overview of the types of instruments developed and tested for validity based on a questionnaire and the content/variable domains in the instrument.PRISMA was used as a guideline in the systemic literature review of this study. Pubmed is search databases with the keywords "validity" AND "nutrition" AND "instrument" AND "woman." The articles obtained at the outset went through a process of searching, screening, eligibility criteria, data extraction, and data synthesis. So that in the end, there were six that studied the types of instruments produced by each study, the method of instrument development, domain, validity, and reliability.Instruments resulting from the studied studies include the Chinese version of the Intention to Eat Low-GI foods questionnaire (CIELQ), Improving Mothers for Better Prenatal Care trial Barcelona (IMPACT BCN), project-level Women's Empowerment in Agriculture Index (pro- WEAI+HN), Nutrition literacy assessment instrument for pregnant women in China (NLAI-P). There are two that are not given a name. Population and sample, women aged 16-50 with late adolescent characteristics, pregnant women, and adult women. Confirmatory factor analysis (CFA) and Cronbach's alpha were used to test the validity and reliability. Nutritional instruments to prevent stunting in women have yet to be developed but to develop these instruments, one can adopt development paths, methods, content domains, validity, and reliability from the results of the literature review in this article.